PENGARUH DISIPLIN, KOMPENSASI, STRES KERJA TERHADAP KINERJA KARYAWAN PT SUMBER ALFARIA TRIJAYA TBK AREA PURWOKERTO - Sopan saeful; Kundaru hadiyato; Endang Sri W (FEB UNWIKU PURWOKERTO, 2020)
This study entitled The Effect of Discipline, Compensation, Job Stress on Employee Performance at PT SumberAlfariaTrijayaTbkPurwokerto Area. The purpose of the study was: to analyze the influence of work discipline, compensation and work stress on the performance of employees of PT SumberAlfariaTrijayaTbk. The analytical tool used is multiple linear regression analysis and hypothesis testing using t test calculations.Based on the results of the study it is known that work discipline, compensation and work stress have a significant influence on employee performance at PT SumberAlfariaTrijayaTbkPurwokerto. The existence of these influences shows that the higher the work discipline on employees, will make their performance increase, so the first hypothesis is accepted. The implication of this research is that increasing employee performance can be improved by increasing work discipline on employees. Things that can be done include improving the ability of employees to do training so that employees are able to work effectively and efficiently. To improve employee performance, companies can also do this by holding vacations to reduce employee saturation. Performance on employees can be done by reducing work stress on employees. things that can be done, among others, by providing work in accordance with their respective job jobs so that there is no accumulation of work activities